Occurrence of Halogenated and Organophosphate Flame Retardants in Sediments and Eels (Anguilla anguilla) From Bizerte Lagoon, Tunisia - Mekni, Sabrine; Barhoumi, Badreddine; Touil, Soufiane; Driss, Mohamed Ridha; Eljarrat, Ethel (Frontiers in Environmental Science, 2020)
Contamination by classic (polybromodiphenyl ethers, PBDEs) and emerging halogenated flame retardants (HFRs) like pentabromobenzene (PBEB), hexabromobenzene (HBB), decabromodiphenyl ethane (DBDPE), and halogenated norbornenes (HNs), as well as organophosphate flame retardants (OPFRs) were investigated in sediment and eel (Anguilla Anguilla) samples from Bizerte Lagoon, northern Tunisia. For sediment samples, HFR levels ranged from 3.30 to 28.5 ng/g dry weight (dw), with a mean value of 10.6 ± 4.36 ng/g dw, while OPFR levels ranged between 9.77 and 164 ng/g dw, with a mean value of 53.6 ± 10.5 ng/g dw. As regards levels in fish, concentration of HFRs ranged between 4.72 and 151 ng/g lipid weight (lw) (mean value of 36.5 ± 28.5 ng/g lw), and OPFR levels ranged between 19.7 and 2,154 ng/g lw (mean value of 404 ± 367 ng/g lw). This is the first time that OPFR levels have been reporting in this area, being higher than those for HFRs. Statistical analysis of the relationship between OPFR and HFR concentrations in sediment and total organic carbon (TOC) was examined. Results suggested that OPFR levels were significantly correlated with TOC, whereas no correlation was found for HFRs and TOC. The health risk associated by the consumption of eel in Bizerte city was assessed and posed no threat to public health concerning PBDE and OPFR intakes.